Comparative toxicity of chlorpyrifos: Sublethal effects on enzyme activities and histopathology of Mugil cephalus and Chanos chanos. (November 2018) - Marigoudar, S.R.; Nagarjuna, A.; Karthikeyan, P.; Mohan, D.; Sharma, K.V.
Abstract: Ecotoxicological data and potential impact of chlorpyrifos (CPF) in the region are scarce for prescribing safety limits. Therefore, toxicity and sublethal impact of CPF on fish fingerlings of Mugil cephalus (3.0 ± 1.2 cm) and Chanos chanos (3.0 ± 1.5 cm) were studied. Acute and chronic toxicity tests were conducted by continuous flow through method and derived 96 h median lethal concentration (LC50 ). Mean LC50 value of 1.13 μg/L for M. cephalus, and 3.20 μg/L for C. chanos were derived by Probit. Chronic toxicity tests were conducted for 30 days and determined no observed effect concentration values of 0.09 μg/L 0.17 μg/L and lowest observed effect concentration values of 0.16 μg/L 0.32 μg/L and chronic values of 0.13 μg/L 0.25 μg/L for M. cephalus and C. chanos respectively. Key biomarker enzyme activities viz., EST, SOD and MDH were studied at sublethal concentrations of CPF. Native gel electrophoresis revealed gradual decrease in isoforms of EST and SOD activities, whereas MDH activity increased in fingerlings. These responses indicate inhibition of cholinesterase, antioxidants and synthesis of ATPs in the cells due to CPF stress. Pathological lesions were evaluated in gill and eye tissues of fingerlings. Epithelial fusion and degenerative changes were prominent in primary lamellae. Hyperplasia, lifting epithelium, fusion of lamellae and necrosis were evidenced in the secondary lamellae. Cellular anomalies in the retina of the eye of C. chanos include vacuoles in nerve fiber layer, shrinkage of outer plexiform layer and detachment of pigment epithelium layer. These changes indicate physiological disturbance in the gill and eye. Graphical abstract: Image 1 Highlights: Fingerlings of Mugil cephalus is relatively sensitive than Chanos chanos to CPF. Cellular anomalies in gill and eye indicated impairment in their physiology by CPF. Native gel electrophoresis revealed that, CPF affects the key enzyme activities.